L'accrétion littorale sur la côte Ouest de Madagascar - Jean-Noël Salomon (Physio-Géo)
géomorphologie, sédimentation, accrétion, littoraux, ligne de rivage, marais maritimes, deltas, MadagascarMadagascar constitutes a good example of an island where generally the shore accretion remains ahead in many areas than the opposite phenomena of retreat of the shore line. After underlining the combination of favourable factors for this tendency, the author draws up a typology of propitious areas for the shores growth and examines through many examples the different types of process that govern these phenomena. The exceptional dynamism and the rapidity of the occidental coastal evolution of Madagascar are not without ecological and economical consequences for the State of Madagascar.